Benefit and toxicity of programmed death‐1 blockade vary by ethnicity in patients with advanced melanoma: an international multicentre observational study. (1st September 2022) - Bai, Xue; Shoushtari, Alexander N.; Betof Warner, Allison; Si, Lu; Tang, Bixia; Cui, Chuanliang; Yang, Xiaoling; Wei, Xiaoting; Quach, Henry T.; Cann, Christopher G.; Zhang, Michael Z.; Pallan, Lalit; et al.
Abstract: Background: Programmed cell death receptor‐1 (PD‐1) monotherapy is a standard treatment for advanced cutaneous melanoma, but its efficacy and toxicity are defined in white populations and remain poorly characterized in other ethnic groups, such as East Asian, Hispanic and African. Objectives: To determine the efficacy and toxicity of PD‐1 monotherapy in different ethnic groups. Methods: Clinical data for patients with unresectable or advanced melanoma treated with anti‐PD‐1 monotherapy between 2009 and 2019 were collected retrospectively from five independent institutions in the USA, Australia and China. Tumour response, survival and immune‐related adverse events (irAEs) were compared by ethnicity (white vs. East Asian/Hispanic/African) across different melanoma subtypes: nonacral cutaneous (NAC)/unknown primary (UP) and acral/mucosal/uveal. Results: In total, 1135 patients were included. White patients had significantly higher objective response rate (ORR) [54%, 95% confidence interval (CI) 50–57% vs. 20%, 95% CI 13–28%; adjusted P < 0·001] and longer progression‐free survival (14·2 months, 95% CI 10·7–20·3 vs. 5·4 months, 95% CI 4·5–7·0; adjusted P < 0·001) than East Asian, Hispanic and African patients in the NAC and UP subtypes. White ethnicity remained independently associated with a higher ORR (odds ratio 4·10, 95% CI 2·48–6·81; adjusted P < 0·001) and longer PFS (hazard ratio 0·58, 95% CI 0·46–0·74; adjusted P < 0·001) in multivariate analyses after adjustment for age, sex, primary anatomical location, metastasis stage, baseline lactate dehydrogenase level, mutational status and prior systemic treatment. White and East Asian/Hispanic/African patients shared similar ORR and progression‐free survival in acral/mucosal/uveal melanomas. Similar melanoma‐subtype‐specific ethnic discrepancies were observed in complete response rate and overall survival. White patients had higher rates of gastrointestinal irAEs but lower rates of endocrine, liver and other rare types of irAEs. These differences in irAEs by ethnicity were not attributable to varying melanoma subtypes. Conclusions: Ethnic discrepancy in clinical benefit is specific to melanoma subtype, and East Asian, Hispanic and African patients with NAC and UP melanomas have poorer clinical benefits than previously recognized. The ethnic discrepancy in toxicity observed across different melanoma subtypes warrants an ethnicity‐based irAE surveillance strategy. More research is needed to elucidate the molecular and immunological determinants of these differences. What is already known about this topic? There is a great difference in response to immunotherapy between different subtypes of melanoma (cutaneous, mucosal, acral and uveal) in patients with advanced disease. What does this study add? Our data show for the first time that there are differences between different ethnic groups in terms of both response and toxicity to immunotherapy beyond the well‐appreciated discrepancies due to melanoma subtype. Abstract: Ethnicity is independently correlated with the clinical benefit and irAEs to anti‐PD‐1 monotherapy, and the differences in clinical benefit by ethnicity are attributed to melanoma subtypes but not irAEs. Caucasian ethnicity is independently associated with better ORR/PFS in NAC/UP but shared similar ORR/PFS in acral/mucosal/uveal melanomas. Caucasians had higher rates of GI but lower rates of endocrine/liver/other‐rare‐types of irAEs regardless of melanoma subtype. Linked Comment: P. Schummer and B. Schilling. Br J Dermatol 2022; 187 :283–284.